Asas Filosofi Dalam Pengembangan Kurikulum Pendidikan Agama Islam - Roslaeni, Ema; Irawan, Irawan (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
There are various factors that are specific problems in it, including teachers, communities, principals, costs and bureaucracy. While in the general problem there are several factors, namely: Scope, Relevance, Balance, Articulation, Integration, Sequence, Continuity, and Transferability. This paper aims to find out the philosophical principles in the development of Islamic religious education curriculum. This writing method uses literature review and processes data with descriptive analysis objectively and systematically.  The results of this study are the philosophical principles in curriculum development have philosophical goals and national education is used as a basis for formulating institutional goals in producing the curriculum of educational institutions.